2005
DOI: 10.1093/ajcn/82.5.1059
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary cachexia, systemic inflammatory profile, and the interleukin 1β −511 single nucleotide polymorphism

Abstract: In COPD patients, who are characterized by an elevated systemic inflammatory response, cachexia is not discriminatory for the extent of increase in inflammatory status. This study, however, indicates a potential influence of genetic predisposition on the cachexia process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
2
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 48 publications
5
84
2
9
Order By: Relevance
“…Similarly, Schols and colleagues found that REE, when adjusted for fat-free mass, was higher in patients with COPD who lost weight compared with those whose weight remained stable (23). Serum levels of TNF-a are higher in cachectic patients with COPD compared with noncachectic patients with COPD and healthy control subjects (24,25), and elevations in IL-1 and IL-6 may also play a role in the development of cachexia (26,27). Reductions in circulating levels of testosterone, growth hormone, insulin-like growth factor, and leptin have also been found in cachectic patients with COPD (21,22,25).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Schols and colleagues found that REE, when adjusted for fat-free mass, was higher in patients with COPD who lost weight compared with those whose weight remained stable (23). Serum levels of TNF-a are higher in cachectic patients with COPD compared with noncachectic patients with COPD and healthy control subjects (24,25), and elevations in IL-1 and IL-6 may also play a role in the development of cachexia (26,27). Reductions in circulating levels of testosterone, growth hormone, insulin-like growth factor, and leptin have also been found in cachectic patients with COPD (21,22,25).…”
Section: Discussionmentioning
confidence: 94%
“…Tumour necrosis factor-a Plasma tumour necrosis factor (TNF)-a and its soluble receptor are increased in COPD patients [13][14][15], and TNF-a is also released from circulating cells in COPD patients with cachexia [16]. Circulating TNF-a appears to be related, at least in part, to hypoxaemia [14].…”
Section: Interleukin-6mentioning
confidence: 99%
“…IL-1b has also been linked to cachexia, but increased plasma concentrations or decreased concentrations of its endogenous antagonist IL-1 receptor antagonist have not been found in COPD, although there is an association between COPD and a polymorphism of the IL-1b gene [15].…”
Section: Il-1bmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inconsistent results have been reported (Ishii et al, 2000;Asada et al, 2005;Hegab et al, 2005;Broekhuizen et al, 2005;Shi et al, 2006;Danilko et al, 2007;Lee et al, 2008;Trajkov et al, 2009;Liu et al, 2012;Shukla et al, 2012;Sun et al, 2013;Issac et al, 2014), which may be because of differences in ethnicity and sample size between studies, resulting in lower statistical power. Meta-analysis may be useful for pooling independent statistical powers and thus achieving a quantitative understanding of the associations.…”
Section: Introductionmentioning
confidence: 98%